The ‘dissonant’ heritage of Nowa Huta’s shelters: Between education and entertainment - Banaszkiewicz, Magdalena; Semik, Zbigniew (Turyzm/Tourism, 2019)
The following article attempts to show how the heritage space of Nowa Huta undergoes gradual transformation under the influence of tourism. An example, which is going to be examined, is a new tourist route presenting the heritage of shelters at Nowa Huta. The context for this discussion is the concept of edutainment, which is a form of education through entertainment. It will be discussed that the inclusion of entertainment elements in the process of dissonant heritage interpretation, is a solution that facilitates noticing ambivalences resulting from the complex nature of the past, and thus contributes to more profound understanding and opens a space for the acceptance of the heritage.